Strategi Guru dalam Menanamkan Karakter Sopan Santun Peserta Didik di SMPN 22 Surakarta - Andara, Yolanda; Listyaningsih (Kajian Moral dan Kewarganegaraan, 2025)
The character of politeness is one of the moral values ​​that must be instilled in the world of education, especially in schools. This study aims to analyze the strategies used by teachers in instilling politeness in students at SMP Negeri 22 Surakarta and identify supporting and inhibiting factors in the process. This study uses a qualitative approach with a descriptive method. Data analysis techniques using Miles and Huberman data collection, data reduction, data display, and conclusion drawing/verification. The focus of the research in this study is the strategies used by teachers in instilling politeness in students and ensuring students that the teachers have implemented the instillation of politeness by the teaching module. Data were obtained through observation, interviews with Pancasila Education teachers, Guidance and Counseling teachers, and the Deputy Head of Student Affairs, as well as documentation. The results of the study showed that the strategies implemented by teachers in instilling politeness include providing exemplary examples, habituation, persuasive approaches, and giving warnings and sanctions in an educational manner. Supporting factors in instilling politeness include school support, parental involvement, and a conducive learning environment. However, there are several inhibiting factors, such as the influence of the environment outside the school, lack of attention from the family, and technological developments that can hurt the character of students. This study uses the behaviorist theory of B.F. Skinner emphasizes that individual behavior can be formed through stimulus and response and strengthened by reinforcement. Keywords: Strategies, Character Education, Politeness.